(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Direct conversion of solar irradiance into electricity can be used as electrical power source for home to meet its daily energy requirement. This paper presents the complete design of a stand-alone Photovoltaic system (SAPV) to supply electric power for a traditional house in city of Misrata-Libya according to its energy requirements. This paper outlines in detail the procedure for specifying each component of the standalone photovoltaic power system. This system can be installed on the roof and the south side of the cabin. The results show that the sizing of PV stand-alone system depends on the load data, the solar resource data and the investment cost of system components. To power these appliances, 79 strings of one with average daily energy of 13.9 kWh. In addition, 52 batteries in the battery bank with system battery capacity of 1300 Ah and voltage 48V, and one charge controller are required. Simulation results and analyses are presented to validate the proposed system configuration.